The Efficacy of Remdesivir in Reducing SARS-CoV-2 Viral Load and Its Safety on COVID-19 Patients: A Systematic Review - Afifah Fauziyyah; Ratika Rahmasari; Rani Sauriasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: This study aimed to examine the effectiveness of Remdesivir in reducing Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) viral load and its safety for antiviral therapy in Coronavirus disease 2019 (COVID-19) treatment.Methods: This systematic review used data sources from the PubMed, ProQuest, SpringerLink, and ClinicalTrial.gov databases for relevant observational and interventional studies during August 2020 to August 2021. Studies evaluating Remdesivir in adults hospitalized for COVID-19 were included in this review. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guidelines.Results This review found 9 studies that were relevant to the study objectives. In total, 1,088 patients participated as subjects. Three studies demonstrated the effect of remdesivir in reducing SARS-CoV-2 viral load in upper and lower respiratory tract specimens. Six studies demonstrated that remdesivir was safe for use in a variety of baseline conditions (patients on hemodialysis and patients receiving kidney transplantation), had no significant hepatotoxicity, did not increase the risk of acute kidney injury, and did not increase eGFR or systemic symptoms in patients taking remdesivir.Conclusion: Remdesivir has been shown to reduce SARS-CoV-2 viral load and was safe for use as antiviral therapy in the treatment of COVID-19, but an assessment of randomized controlled trial for the effect of Remdesivir on viral load reduction was not available yet.